2014
DOI: 10.1186/1471-2229-14-107
|View full text |Cite
|
Sign up to set email alerts
|

Homologous haplotypes, expression, genetic effects and geographic distribution of the wheat yield gene TaGW2

Abstract: BackgroundTaGW2-6A, cloned in earlier research, strongly influences wheat grain width and TKW. Here, we mainly analyzed haplotypes of TaGW2-6B and their effects on TKW and interaction with haplotypes at TaGW2-6A.ResultsAbout 2.9 kb of the promoter sequences of TaGW2-6B and TaGW2-6D were cloned in 34 bread wheat cultivars. Eleven SNPs were detected in the promoter region of TaGW2-6B, forming 4 haplotypes, but no divergence was detected in the TaGW2-6D promoter or coding region. Three molecular markers including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
92
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 59 publications
9
92
1
Order By: Relevance
“…Evidence of selection was supported by changes in haplotype frequencies in the last 60 years. We found differences between haplotypes at the same locus influence selection time and intensity Qin et al 2014). S6).…”
Section: Discussionmentioning
confidence: 76%
“…Evidence of selection was supported by changes in haplotype frequencies in the last 60 years. We found differences between haplotypes at the same locus influence selection time and intensity Qin et al 2014). S6).…”
Section: Discussionmentioning
confidence: 76%
“…Among these 30 genes, 26 are located in the candidate region mapped by at least one method (SLM, JLM, and GWAS) in the RIL populations and five were found to be significantly associated with kernel traits by candidate gene association mapping in a large association panel. Given the conserved functions of many of the known genes for kernel development in maize, rice, and wheat (Su et al, 2011;Hong et al, 2014;Qin et al, 2014;Jaiswal et al, 2015;Wang et al, 2015Wang et al, , 2016Ma et al, 2016;Simmonds et al, 2016), these genes represent additional candidates for kernel development across various species.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Liu et al (2015) showed that GS5 contributes to kernel size variation in maize as well as in rice. Notably, the wheat orthologs of rice GW2 and GS5 also were associated significantly with wheat kernel size and weight (Su et al, 2011;Hong et al, 2014;Qin et al, 2014;Jaiswal et al, 2015;Wang et al, 2015Wang et al, , 2016Ma et al, 2016;Simmonds et al, 2016). In addition to GS3, GW2, and GS5, many other genes controlling rice kernel size/weight have been cloned, such as genes involved in G-protein signaling (DEP1 and D1) and genes from phytohormone pathways (DST and Gn1a for cytokinin; D11, SRS5, D61, qGL3, and SMG1 for brassinosteroid; and TGW6 for auxin).…”
mentioning
confidence: 99%
“…10 gene had functions that affect the TGW, PH and SL during the maturity stage. To date, some grain weight genes have been isolated, such as Ppd-D1 [56], CKX6-D1 [57], GS1a [11], GW2 [8, 5859], GS-D1 [60], Sus [9, 61], GASR7 [6263], TEF-7 [64], CWI [65], and 1-FEH-w3 [6667]. Using sequence comparison and the analysis of protein domains with PROSITE (http://prosite.expasy.org/), we found that TaSnRK2 .…”
Section: Discussionmentioning
confidence: 99%